Qualitative Behavioural Assessment as a Method to Identify Potential Stressors during Commercial Sheep Transport - Teresa Collins; Catherine A. Stockman; Anne L. Barnes; David W. Miller; Sarah L. Wickham; Patricia A. Fleming (Animals, 2018)
Land transport is an unavoidable experience for most livestock, yet there is limited research comparing animal welfare under different conditions. We video recorded sheep responses during short (2 h) commercial road transport journeys. Using Qualitative Behavioural Assessment, observers (blinded to the treatments) scored the behavioural expression of sheep and reached significant consensus in their scoring patterns (p < 0.001). There were also significant effects of vehicle crate design (sheep transported in a ‘standard’ crate were more calm/relaxed than those transported in a ‘convertible’ crate), deck position (sheep on upper decks were more curious/alert than those on lower decks), and sheep breed (fat-tail sheep were more agitated/distressed than merino sheep) on observer scores. We only found marginal differences for sheep originating from feedlot or saleyard. Significant effects of vehicle driver (included as a random factor in all but one of our analyses) suggest driving patterns contributed to demeanour of the sheep. Finally, the fourteen drivers who participated in the study were asked their opinions on livestock transport; none of the factors we tested were identified by drivers as important for sheep welfare during transport. This study supports the use of qualitative measures in transport and revealed differences that could inform truck design.